Polycentric and Reflexive Governance: Adaptive Strategies for Renewable Energy Management - Afina Nadhira Yuvani Putri (Adaptive Governance Research, 2025)
Purpose: This study examines the implementation of polycentric and reflexive governance in renewable energy management in Indonesia, focusing on stakeholder interactions, adaptive governance mechanisms, and collaborative decision-making processes. Subjects and Methods: This study employed a qualitative descriptive case study approach involving 20 purposively selected participants, including government officials, project managers, NGO representatives, private sector actors, policy experts, and community leaders. Data were collected through semi-structured interviews, document analysis, and descriptive survey support. The data were analyzed using thematic analysis supported by NVivo-assisted coding, categorization, and triangulation techniques. Results: The findings indicate that polycentric governance enhances flexibility, stakeholder participation, and responsiveness in renewable energy projects, particularly in decentralized and community-based initiatives. Trust-building mechanisms, transparent communication, and cross-sectoral collaboration were identified as critical factors supporting governance effectiveness. Reflexive governance also strengthened institutional adaptability through continuous learning and policy adjustment under changing environmental and socio-political conditions. However, institutional limitations, regulatory inconsistency, and stakeholder conflicts remained significant challenges. Conclusions: The integration of polycentric and reflexive governance contributes to adaptive and inclusive renewable energy management by strengthening coordination, collaboration, and governance resilience across multiple institutional levels.